Antioxidant and Antibacterial Activities of Curd and Whey Kefir Produced from Etawa Goat Milk - Siwi Meutia Sadewi; Nurhasanah Nurhasanah; Sudibyo Sudibyo; Neneng Windayani; Agung Abadi Kiswandono; Heri Satria (Pandawa Institute, 2024)
Kefir is a fermented drink with many benefits. Kefir contains antioxidant compounds that can inhibit free radical activity.In addition, kefir contains lactic acid bacteria, which provide good antibacterial activity and improve the health of the digestive tract. This research aimed to determine the antioxidant and antibacterial activities of kefir made from Etawa goat milk. The methods used in this research included fermentation of Etawa goat milk with 10 % kefir seeds at 37 °C and a fermentation time of 2 days. Antioxidant activity was tested using 1,1-diphenyl-2-picrylhydrazyl (DPPH), and antibacterial activity was tested using agar diffusion. The peptide molecular weights in kefir were analyzed using SDS-PAGE. The results showed that the antibacterial and antioxidant activities in Etawa goat's milk curd kefir has a higher activity than whey kefir. The antioxidant activity of curd has an IC50 of 43.99 ppm, which is a powerful antioxidant. Curd's antibacterial activity forms a clear zone of 7 mm against Bacillus cereus and is included in the solid antibacterial category. In Escherichia coli, a clear zone of 6 mm was formed and included in the moderate antibacterial category. The results of SDS-PAGE gel visualization found three prominent bands measuring 10, 15, and 33 kDa, respectively.